Productivity and Cost of Tree-length Harvesting Using Cable Yarding System in a Larch (Larix leptolepis) Clear-cutting Stand - 정응진; 조구현; 조민재; 최병구; 차두송 (Journal of forest and environmental science , 33(2), 2017)
The purpose of this study was to examine productivity and cost of tree-length harvesting using cable yarding system in a larch (Larix leptolepis) clear-cutting stand located in Pyeongchang-gun, Gangwon-do. We used tree-length harvesting method using cable yarding system with a tower yarder HAM300. The productivity was 17.6 m3/hr for felling, 12.4 m3/hr for delimbing, 4.2 m3/hr for yarding, and 8.1 m3/hr for processing. The total cost of the harvesting system was 48,381 won/m3, which was majorly composed of yarding operation cost, at 40,169 won/m3 (79.3%), while felling had the lowest cost at 1,154 won/m3 (4.1%). Major factors affecting felling and processing productivity was tree volume and the number and thickness of branches for delimbing productivity. In addition, we suggest that training and education for machine operators were critical to improve yarding productivity. KCI Citation Count: 0